2020
DOI: 10.1002/ccd.29098
|View full text |Cite
|
Sign up to set email alerts
|

Transradial access in acute myocardial infarction complicated by cardiogenic shock: Stratified analysis by shock severity

Abstract: Background Transradial access (TRA) is associated with improved survival and reduced vascular complications in acute myocardial infarction (AMI). Limited data exist regarding TRA utilization and outcomes for AMI complicated by cardiogenic shock (CS). We sought to assess the safety, feasibility, and clinical outcomes of TRA in AMI‐CS. Methods One‐hundred and fifty‐three patients with AMI‐CS were stratified into tertiles of disease severity using the CardShock score. The primary endpoint was successful percutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Although, it is difficult to argue with prior randomized trials showing reduced bleeding and improved mortality with radial access in the AMI population, a more recent randomized trial of >2000 AMI patients from North America showed minimal differences in outcomes between radial and femoral arms 5 . Importantly, the highly significant, four‐fold improvement in access site bleeding and vascular complications observed with ultrasound guided femoral access in the current study, 1 is reassuring that use of the femoral artery for cardiogenic shock interventions remains a reasonable alternative, if meticulous care is given to access technique.…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…Although, it is difficult to argue with prior randomized trials showing reduced bleeding and improved mortality with radial access in the AMI population, a more recent randomized trial of >2000 AMI patients from North America showed minimal differences in outcomes between radial and femoral arms 5 . Importantly, the highly significant, four‐fold improvement in access site bleeding and vascular complications observed with ultrasound guided femoral access in the current study, 1 is reassuring that use of the femoral artery for cardiogenic shock interventions remains a reasonable alternative, if meticulous care is given to access technique.…”
mentioning
confidence: 45%
“…In this issue of the journal, Tehrani et al reported a retrospective study of 153 patients with acute myocardial infarction (AMI) associated cardiogenic shock (CS) treated at a single high volume shock center 1 . Radial access for coronary angiography was used in 53%, and usually applied to patients with less severe CS.…”
mentioning
confidence: 99%
“…Acute ischemic limbs and major vascular complications during cardiogenic shock admission were as high as 10%, which led to accelerated development of short-and long-term adverse outcomes. 5 Despite this variability in the estimates, which could be explained by a large heterogeneous study population, variability in the definition of exposures and outcome inherent to claims datasets, and the application of causal inference techniques, this study highlights an important fact: bleeding and vascular injury remain an important outcome in interventional cardiology, but even more for those with cardiogenic shock. Because significant variability in care for cardiogenic shock exists in practice within different regions of the United States and worldwide, several initiatives by academic consortiums, endorsed by the Food and Drug Administration (FDA), are actively engaged to address clinical problems that have a large impact on outcomes in patients with cardiogenic shock.…”
mentioning
confidence: 85%
“…Similarly, in an observational study, one in three patients develop major bleeding events secondary to large‐bore access used for mechanical circulatory support devices. Acute ischemic limbs and major vascular complications during cardiogenic shock admission were as high as 10%, which led to accelerated development of short‐ and long‐term adverse outcomes 5 …”
mentioning
confidence: 99%
“…139 In contemporary practice, bleeding risk is reduced by the use of radial access, even among patients presenting with cardiogenic shock. 148,149 Bleeding risk is further reduced with the use of the latest generation drug-eluting stents and shorter duration of DAPT. 150,151 The SENIOR trial showed that in older adults with high bleeding risk, patients treated with drug-eluting stents and short-duration DAPT had a lower incidence of the composite end point of all-cause death‚ MI, stroke, or urgent revascularization compared with patients treated with bare-metal stents and short-duration DAPT with no difference in risk of bleeding.…”
Section: Percutaneous Revascularization In Older Adultsmentioning
confidence: 99%